Association of Cushing Syndrome's Emotional Distress and Cognitive Symptoms with Cortisol Levels - Humaira Sami Ullah, Mohammed Ibrahim, Atiq Ahmad, Neha Ahuja, Muhammad Usman, Aamir Nazir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cushing's syndrome is a rare endocrine disorder characterized by excess cortisol levels, leading to physical, emotional and cognitive symptoms. The syndrome can result from various causes, it is most commonly due to prolonged corticosteroid use, but endogenous causes can include tumors of adrenal gland, pituitary gland or ectopic adrenocorticotropic hormone producing tumors. Objective: To determine the association of Cushing syndrome’s emotional distress and cognitive symptoms with cortisol levels. Study Design: Retrospective study Place and Duration of Study: Medical Unit-2, Bolan Medical Complex Hospital, Quetta from 1st Jan 2009 to 31st July 2023. Methodology: Fifty patients diagnosed with Cushing's syndrome, aged 25-40 years, with chronic hypercortisolism were enrolled. Patients with a history of psychiatric illness were excluded. The diagnosis was confirmed through either 24-hour urinary free cortisol, and/or dexamethasone suppression, late night salivary cortisol tests. Patients were categorized into "Cases" (high cortisol and emotional symptoms) and "Controls" (high cortisol, minimal emotional symptoms). Results: High cortisol levels were significantly associated with cognitive and emotional distress symptoms (p=0.021).Emotional complaints, particularly anxiety, sadness, and emotional liabilities, were more prevalent in cases with high cortisol levels. The cognitive symptom most commonly seen was disturbance of memory. But attention, word finding and processing speed were also more commonly affected with high cortisol levels. Treatment outcomes varied between cases and controls, with pituitary-directed medical treatment being more common in controls (40%) than cases (14.2%). Conclusion: There is a significant association between high cortisol levels, cognitive and emotional distress symptoms in Cushing's syndrome patients. Keywords: Cushing syndrome, Cognitive, Cortisol, Emotional distress, Quality of life